Career decision-making readiness among students’ in the system of higher education: career course intervention - Azhenov, Askar; Kudysheva, Ainash; Fominykh, Nataliia; Tulekova, Gulmira (Frontiers in Education, 2023)
Career decision-making is a complicated process in which students must understand themselves. In this paper, the influence of the implemented “Career development” course on the Toraighyrov University undergraduate students’ readiness for career decision-making was analyzed. The Career Decision-making Difficulties Questionnaire (CDMDQ) and it was used to test the hypothesis that by implementing “Career Development” course the level of students’ career decision-making readiness would increase. The participants were 104 students at Toraighyrov University, divided equally into the control and experimental groups (52 students each). The experimental group, unlike the control group, took the “Career Development” course for 15 weeks. Students were randomly chosen from humanities (psychology, education, journalism, and social work) and Science, Technology, Engineering, and Mathematics (electrical engineering, computer science, and metallurgical engineering) fields. The average age of participants was 21 years. The results show that there is significant difference in pre-course and post-course testing in each of the career decision-making difficulties cluster: (1) Lack of Readiness; (2) Lack of Information and (3) Inconsistent information in experimental in comparison to control group.